Kurikulum dan pembelajaran berbasis kesejahteraan semesta - Ari Kamayanti; Novrida Qudsi Lutfillah (Forum Dosen Ekonomi dan Bisnis Islam (FORDEBI), 2020)
This paper aims to provide curriculum suggestions and forms of learning that are able to make every human being the result of learning become a manifestation of the Universal Welfare architecture. From criticizing the economic, management, and Islamic / Sharia accounting curricula, it can be seen that it is not enough just to